Liars' paradox - Stevens, Taylor (Stevens, Taylor. Jack and Jill thriller., 2019)
"They live in the shadows, Jack and Jill, feuding twins who can never stop running. From earliest memory they've been taught to hide, to hunt, to survive. Their prowess is outdone only by Clare, who has always been mentor first and mother second. She trained them in the art of espionage, tested their skills in weaponry, surveillance, and sabotage, and sharpened their minds with nerve-wracking psychological games. As they grew older they came to question her motives, her methods--and her sanity. Now twenty-six years old, the twins are trying to lead normal lives. But when Clare's off-the-grid safehouse explodes and she goes missing, they're forced to believe the unthinkable: Their mother's paranoid delusions have been real all along. To find her, they'll need to set aside their differences; to survive, they'll have to draw on every skill she's trained them to use. A twisted trail leads from the CIA, to the KGB, to an underground network of global assassins where hunters become the hunted. Everyone, it seems, wants them dead--and, for one of the twins, it's a threat that's frighteningly familiar and dangerously close to home"--